Development E-Module For Stock Making In The Basic Culinary In Vocational High Schools - Tiara Nur Afifah; Rina Setyaningsih; Ika Wahyu Kusuma Wati (Jurnal Pendidikan Tata Boga dan Teknologi, 2026)
This research is motivated by the limitations of learning media used in SMK Negeri 1 Sewon Bantul, so that students feel bored and have difficulty understanding the material delivered by the teacher. The objectives of this study are: 1) to develop an e-module media for stock making, 2) to determine the feasibility of material experts and media experts regarding the e-module media for stock making, 3) to determine students' responses to the use of e-module media for stock making. The type of research is research and development (R&D) with the Four-D model (Define, Design, Development, Dissemination). Data collection techniques are observation, questionnaires and documentation. Data analysis techniques use descriptive statistical analysis. The results of the study show that: 1) this study produces an e-module learning media for stock making in the form of a flipbook heyzine link https://heyzine.com/flipbook/c70ef8e0de.html; 2) The stock making e-module media was declared very suitable for use, based on the validation results of material experts with a percentage of 84,36% and media experts with a percentage of 96,7%; 3) the students' responses to the stock making e-module media showed a very understanding category, based on small scale trials with a percentage of 88,13% and on limited scale trials with a percentage of 87,88%.